Pangeran Diponegoro Pahlawan Nasional dalam Novel Remy Sylado sebagai Sumber Belajar Sejarah - Isrina Siregar; Wahyuningtyas Kurniawati (Universitas Batanghari Jambi, 2023)
The quality of education in Indonesia is declining, one of the reasons is that character education is still not optimal in schools, history learning resources so far have only used artifacts and other historical relics. Even though in the process of learning novels can be used as a source of learning history. Characters in historical novels can be used as a tool for instilling student character values. The method used in this study is a qualitative method with a historical or historical approach. The main data source used in this research is the novel Prince Diponegoro by Remy Sylado, published by Tiga Serangkakai. This study found several character values contained in the Prince Diponegoro novel, namely religion, nationalism values (love of the motherland), social care values, and cultural values. The value of character education can be used as a source of learning history that can be collaborated in basic competencies in class XI high school, namely 3.6 Analyzing the role of national and regional figures in fighting for Indonesian independence.